Relationship between the quench delay time and tensile properties for various section thicknesses of AA 7075 Al alloy. (2016) - Jayanthi, A.; Kumar, M. Anil; Prabhu, T. Ram
The effects of quench delay time on tensile properties of AA 7075 Al alloy were investigated for various diameters (30, 65, 100, 125 and 165 mm). The bars were kept in air after solution treatment for selected delay time depending on the diameter and were given water quenching and double ageing. Tensile properties and microstructure properties were investigated. The tensile and yield strength properties decrease with increasing the quench delay time and there has been no specific trend observed between the tensile properties and the quench delay time. The drop in the tensile strength may be categorised into three regions: 30-65, 100-125 and 165-200 mm, the strength variation within the region is negligible in contrast to the wide variation observed between the regions, the superimposition of the C curve with the predicted time data explains reasonably the cause of drop in mechanical properties with the diameter.